IMPLEMENTATION OF HIV/AIDS CONTROL POLICY SEMARANG CITY (Based on Semarang City Regional Regulation Number 4 of 2013) - Neysadella Adilina; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro)
HIV/AIDS appears to have disappeared since Covid-19 was declared a global pandemic, despite the fact that its spread continues. The number of people living with HIV/AIDS in the city of Semarang is growing every year. The prevalence of high-risk HIV/AIDS behaviors in key population areas contributes to the increase in HIV/AIDS infections. Furthermore, the general public's understanding of HIV/AIDS prevention, transmission, and management remains limited. The lack of public awareness will almost certainly result in a high negative stigma in society. In this regard, the Semarang City Government established a legal basis, namely the Semarang City Regional Regulation Number 4 of 2013 concerning HIV/AIDS Prevention in the City of Semarang, in response to the large number of HIV/AIDS cases and the lack of public understanding. The purpose of this study is to identify and analyze how HIV/AIDS prevention policies are implemented in the city of Semarang, as well as to determine how far the strategies that have been carried out by the city of Semarang's local government to achieve the successful implementation of these policies have progressed. The descriptive qualitative research method is used in this study. The findings revealed that the implementation of the HIV/AIDS control program in the city of Semarang was quite good, based on the local regulation of the city of Semarang Number 4 of 2013 concerning the prevention of HIV/AIDS in the city of Semarang, namely promotion, prevention, treatment, and social rehabilitation. However, there are still several factors impeding the program's implementation, including underutilized condom distribution activities, PLWHA dropping out of treatment, not all parties involved understanding the contents of the Regional Regulation, and the Covid-19 pandemic factor. As a result, the recommendations that can be made are to increase outreach activities as well as outreach to places where people are at high risk of contracting HIV, and to collaborate with KDS/WPA to approach and assist PLWHA.